2017
DOI: 10.1016/j.virol.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

An interaction domain in human SAMD9 is essential for myxoma virus host-range determinant M062 antagonism of host anti-viral function

Abstract: In humans, deleterious mutations in the sterile α motif domain protein 9 (SAMD9) gene are associated with cancer, inflammation, weakening of the immune response, and developmental arrest. However, the biological function of SAMD9 and its sequence-structure relationships remain to be characterized. Previously, we found that an essential host range factor, M062 protein from myxoma virus (MYXV), antagonizes the function of human SAMD9. In this study, we examine the interaction between M062 and human SAMD9 to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 30 publications
(54 reference statements)
0
37
0
Order By: Relevance
“…SAMD9 and SAMD9L-Very recently, sterile alpha motif domain-containing protein 9 (SAMD9) was shown to be a host innate antiviral factor against poxvirus (e.g. vaccinia and myxoma virus), Japanese encephalitis virus and low-risk Papillomavirus in humans (154)(155)(156)(157)(158)(159). Mutations in SAMD9 and its paralog SAMD9-like (SAMD9L) are associated with a heterogeneous clinical phenotype.…”
Section: Mda5-rare Heterozygous Gof Mutations Of Ifn-induced Helicasementioning
confidence: 99%
“…SAMD9 and SAMD9L-Very recently, sterile alpha motif domain-containing protein 9 (SAMD9) was shown to be a host innate antiviral factor against poxvirus (e.g. vaccinia and myxoma virus), Japanese encephalitis virus and low-risk Papillomavirus in humans (154)(155)(156)(157)(158)(159). Mutations in SAMD9 and its paralog SAMD9-like (SAMD9L) are associated with a heterogeneous clinical phenotype.…”
Section: Mda5-rare Heterozygous Gof Mutations Of Ifn-induced Helicasementioning
confidence: 99%
“…Liu and coworkers (22) described the formation of SAMD9containing granules, which appear related but not identical to typical stress granules, in the absence of C7/K1 of VACV or MO62 of myxoma virus. A mutagenesis study indicated that the N-terminal 385 amino acids of SAMD9 retain the ability to interact with MO62 but are insufficient to prevent replication of the host range mutants (26). SAMD9L, a paralog of SAMD9, also inhibits the C7/K1 mutant (27).…”
mentioning
confidence: 99%
“…The identification of CP77 as yet another SAMD9L inhibitor underscores the critical role of SAMD9&L in host defense against poxviruses and the elaborate lengths OPXVs went to evade SAMD9&L. K1 and C7 were previously shown to function equivalently at inhibiting human and mouse SAMD9&L (25). In this study, however, we uncovered differences between K1/C7/CP77 in their targeting mechanism and binding specificity for SAMD9&L. While a C7 ortholog was shown to target the N-terminus of SAMD9 (39), both K1 and CP77 target an internal region containing the predicated NTPase and TPR domains. While any one of K1/C7/CP77 can bind mouse SAMD9L, only K1 can bind chSAMD9, and only CP77 can bind chSAMD9L.…”
Section: Discussionmentioning
confidence: 87%
“…5A). The N-terminal 385 aa of human SAMD9 (hSAMD9), which contains the predicted SAM and AlbA domains, was reported to be sufficient for binding to a poxvirus C7 homolog (39). To find out which region of hSAMD9 is targeted by K1, we constructed hSAMD9 mutants with deletions in different domains and tested the binding of the mutants to K1.…”
Section: Resultsmentioning
confidence: 99%